Esterification of palm fatty acid distillate using sulfonated carbon-based catalyst derived from palm kernel shell and bamboo - Farabi M.S.A.; Ibrahim M.L.; Rashid U.; Taufiq-Yap Y.H. (Elsevier Ltd, 2024)
Indexed by WOS/Scopus/ERA